2020
DOI: 10.1128/aac.01963-19
|View full text |Cite
|
Sign up to set email alerts
|

VNRX-5133 (Taniborbactam), a Broad-Spectrum Inhibitor of Serine- and Metallo-β-Lactamases, Restores Activity of Cefepime in Enterobacterales and Pseudomonas aeruginosa

Abstract: As shifts in the epidemiology of β-lactamase-mediated resistance continue, carbapenem-resistant Enterobacterales (CRE) and carbapenem-resistant Pseudomonas aeruginosa (CRPA) are the most urgent threats. Although approved β-lactam (BL)–β-lactamase inhibitor (BLI) combinations address widespread serine β-lactamases (SBLs), such as CTX-M-15, none provide broad coverage against either clinically important serine-β-lactamases (KPC, OXA-48) or clinically important metallo-β-lactamases (MBLs; e.g., NDM-1). VNRX-5133 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 50 publications
5
109
0
Order By: Relevance
“…Unlike QPX7728, taniborbactam, does not inhibit class D carbapenemases from A. baumannii (27)(28)(29).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike QPX7728, taniborbactam, does not inhibit class D carbapenemases from A. baumannii (27)(28)(29).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Thus, QPX7728 is a covalent low off-rate inhibitor of serine enzymes. In contrast, inhibition of metallo beta-lactamases by QPX7728 [similar to taniborbactam (27)] proceeds through a simple one-step complex formation typical for "fast on -fast off" inhibitors.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Moreover, several MBL inhibitors, including aspergillomarasmine A (15), dipicolinic acid derivatives (16), ANT431 (17), bisthiazolodines (18) and bismuth antimicrobials (19) have been reported. Recently, VNRX-5133 (taniborbactam), a dual SBL and MBL inhibitor have shown potent activity in combination with cefepime against MBL-producers (20). However, no direct MBL inhibitors are approved for clinical use (21).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many research groups have developed MBL inhibitors and confirmed their activity against purified MBL enzymes in vitro; however, most inhibitors showed extremely low activity toward live MBL-producing bacteria, suggesting that their permeativity of the bacterial outer membrane is low (7). Thus, only a few MBL inhibitors, such as ME1071, developed by Meiji Seika Pharma (8), and cyclic boronates (9,10), including VNRX-5133 (taniborbactam), developed by Venatorx (11)(12)(13), and ANT431, developed by Antabio SAS (14), are reportedly active against MBL-producing clinical isolates. Nonetheless, none of these compounds have been approved for clinical use.…”
mentioning
confidence: 99%